PERANAN ORANG TUA DALAM MEMBENTUK KARAKTER ANAK DI TPQ AL-AMIN KEBONAGUNG MALANG - Mochammad Firdaus; Azhar Haq; Moh Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Every parent expects his son to grow up to be a child of Shaleh. To achieve this, it is necessary to have proper and correct education. In that case, both parents have a very important role. Parents are the first to nurture, raise, guide and educate and have a great influence on the growth and development of the child. Parents are also responsible for shaping their children's character. To find out how the role of parents in shaping children's character in the TPQ Al-Amin Kebonagung Then in this research, researchers use a type of descriptive qualitative study which means that research seeks to relate existing problem solving based on the descriptive qualitative data that is often used to analyze the incidence of phenomenon, or social conditions. Based on the data obtained by researchers thanks to the role of parents in forming children's character in the TPQ Al-Amin with Tauladan, supervision and habituation, then obtained positive results in the form of children who are polite, children become more disciplined, and children have a worship character.